ANALISIS GENDER AND DEVELOPMENT (GAD) TERHADAP MEKANISME BIAS GENDER DALAM PEMILIHAN JURUSAN DI MADRASAH ALIYAH NEGERI - Salmayunicha Listie Putri, Rika Yunianingsih, Dwi Gustavina Syahbani, Maulidha Putri Cahyani, Joseph (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This study aims to analyze gender equality dynamics at MAN 1 Magelang, focusing on how cultural norms and social structures influence subject selection and student experiences. Although formally all subjects are open to both males and females, findings show that stereotypes, subordination, marginalization, and symbolic violence are still reproduced through school culture, teacher guidance, and social perceptions attached to certain fields of expertise. Using the Gender and Development (GAD) approach, this study shows that inequality does not stem from biological abilities, but rather from social constructs that place men and women in different roles. Through qualitative descriptive methods involving interviews, observations, and literature studies, the study found that equal access has not resulted in equal participation because the internalization of patriarchal norms remains strong. The GAD approach has proven relevant in uncovering the roots of inequality and emphasizing the need for a transformation of power relations, changes in school culture, and the strengthening of teacher capacity. This study recommends the integration of gender awareness education and the reconstruction of understanding of gender-based work to create an inclusive and equitable madrasah environment.